Faunal community ecology of central-eastern Indian Ocean Seamounts - Timothy D. O'Hara; Shane T. Ahyong; Phil Alderslade; Dianne Bray; Francesco Criscione; Niki Davey; Caroline Farrelly; Martin F. Gomon; Ana Hara; Jeremy Horowitz; Andrew M. Hosie; Lisa Kirkendale; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Corrigendum to “Systematics of deep-sea starfish order Brisingida (Echinodermata: Asteroidea), with a revised classification and assessments of morphological characters” [Mol. Phylogenetics Evol. 191 (2024) 107993] - Ruiyan Zhang; Marine Fau; Christopher Mah; Marc Eléaume; Dongsheng Zhang; Yadong Zhou; Bo Lu; Chunsheng Wang (Molecular Phylogenetics and Evolution, 2024)

Neurophysiological and other features of working memory in older adults at risk for dementia - Rachel A. Patterson; Heather Brooks; Mina Mirjalili; Neda Rashidi-Ranjbar; Reza Zomorrodi; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Ariel Graff-Guerrero; Nathan Herrmann; James L. Kennedy; Sanjeev Kumar; et al. (Cognitive Neurodynamics, 2024)

Systematics of deep-sea starfish order Brisingida (Echinodermata: Asteroidea), with a revised classification and assessments of morphological characters - Ruiyan Zhang; Marine Fau; Christopher Mah; Marc Eléaume; Dongsheng Zhang; Yadong Zhou; Bo Lu; Chunsheng Wang (Molecular Phylogenetics and Evolution, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

When Imagery and Physical Sampling Work Together: Toward an Integrative Methodology of Deep-Sea Image-Based Megafauna Identification - Mélissa Hanafi-Portier; Sarah Samadi; Laure Corbari; Tin-Yam Chan; Wei-Jen Chen; Jhen-Nien Chen; Mao-Ying Lee; Christopher Mah; Thomas Saucède; Catherine Borremans; Karine Olu (Frontiers in Marine Science, 2021)
Imagery has become a key tool for assessing deep-sea megafaunal biodiversity, historically based on physical sampling using fishing gears. Image datasets provide quantitative and repeatable estimates, small-scale spatial patterns and habitat descriptions. However, taxon identification from images is challenging and often relies on morphotypes without considering a taxonomic framework. Taxon identification is particularly challenging in regions where the fauna is poorly known and/or highly diverse. Furthermore, the efficiency of imagery and physical sampling may vary among habitat types. Here, we compared biodiversity metrics (alpha and gamma diversity, composition) based on physical sampling (dredging and trawling) and towed-camera still images (1) along the upper continental slope of Papua New Guinea (sedimented slope with wood-falls, a canyon and cold seeps), and (2) on the outer slopes of the volcanic islands of Mayotte, dominated by hard bottoms. The comparison was done on selected taxa (Pisces, Crustacea, Echinoidea, and Asteroidea), which are good candidates for identification from images. Taxonomic identification ranks obtained for the images varied among these taxa (e.g., family/order for fishes, genus for echinoderms). At these ranks, imagery provided a higher taxonomic richness for hard-bottom and complex habitats, partially explained by the poor performance of trawling on these rough substrates. For the same reason, the gamma diversity of Pisces and Crustacea was also higher from images, but no difference was observed for echinoderms. On soft bottoms, physical sampling provided higher alpha and gamma diversity for fishes and crustaceans, but these differences tended to decrease for crustaceans identified to the species/morphospecies level from images. Physical sampling and imagery were selective against some taxa (e.g., according to size or behavior), therefore providing different facets of biodiversity. In addition, specimens collected at a larger scale facilitated megafauna identification from images. Based on this complementary approach, we propose a robust methodology for image-based faunal identification relying on a taxonomic framework, from collaborative work with taxonomists. An original outcome of this collaborative work is the creation of identification keys dedicated specifically to in situ images and which take into account the state of the taxonomic knowledge for the explored sites.

Overlooked biodiversity from museum collections: four new species and one new genus of Ophiuroidea (Echinodermata) from Antarctica and adjacent regions with notes on multi-armed ophiuroids - Masanori Okanishi; Christopher L. Mah (Marine Biodiversity, 2020)

Corrigendum: The Unknown and the Unexplored: Insights Into the Pacific Deep-Sea Following NOAA CAPSTONE Expeditions - Brian R. C. Kennedy; Kasey Cantwell; Mashkoor Malik; Christopher Kelley; Jeremy Potter; Kelley Elliott; Elizabeth Lobecker; Lindsay McKenna Gray; Derek Sowers; Michael P. White; Scott C. France; Steven Auscavitch; et al. (Frontiers in Marine Science, 2020)

The Unknown and the Unexplored: Insights Into the Pacific Deep-Sea Following NOAA CAPSTONE Expeditions - Brian R. C. Kennedy; Kasey Cantwell; Mashkoor Malik; Christopher Kelley; Jeremy Potter; Kelley Elliott; Elizabeth Lobecker; Lindsay McKenna Gray; Derek Sowers; Michael P. White; Scott C. France; Steven Auscavitch; et al. (Frontiers in Marine Science, 2019)

Unexplored diversity of the mesophotic echinoderm fauna of the Easter Island ecoregion - Ariadna Mecho; Erin E. Easton; Javier Sellanes; Matthias Gorny; Christopher Mah (Marine Biology, 2019)

Purification of the therapeutic antibody trastuzumab from genetically modified plants using safflower Protein A-oleosin oilbody technology - Michael D. McLean; Rongji Chen; Deqiang Yu; Kor-Zheng Mah; John Teat; Haifeng Wang; Steve Zaplachinski; Joseph Boothe; J. Christopher Hall (Transgenic Research, 2012)

Biodiversity and phylogeography of Arctic marine fauna: insights from molecular tools - Sarah Mincks Hardy; Christina M. Carr; Michael Hardman; Dirk Steinke; Erin Corstorphine; Christopher Mah (Marine Biodiversity, 2011)

Spatial and temporal modulation of joint stiffness during multijoint movement - Christopher D. Mah (Experimental Brain Research, 2001)